The Effect of Maternal Trace Element Status (Copper, Zinc, Selenium, and Chromium) on Neonatal Wellbeing - Saja Karim Toman; Majid Hameed Ahmed; Shaimaa Abdulamir Nasir (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Trace elements such as copper, zinc, selenium, and chromium play essential roles in various enzymatic reactions, antioxidant defense mechanisms, and overall metabolic regulation, making them crucial for maternal and fetal health. During pregnancy, the demand for these micronutrients increases significantly due to physiological changes and the needs of the developing fetus. Inadequate or excessive levels of these trace elements can lead to altered fetal development and may impact neonatal outcomes immediately after birth. Given the sensitive developmental window of gestation, the intrauterine environment—including micronutrient status—has been hypothesized to influence neonatal physiological parameters such as heart rate, respiratory rate, and Apgar scores, which are commonly used to assess neonatal wellbeing in the early minutes of life. This study attempts to explore the impact of maternal trace element status—specifically copper, zinc, selenium, and chromium—along with selected maternal parameters (BMI, parity, gravida) on indicators of neonatal wellbeing, including heart rate, respiratory rate, and 5-minute Apgar score. A cross-sectional study was conducted in the Delivery Room of the Obstetric Hospital in Al-Diwaniya City, Iraq, involving 50 mother-infant pairs. Data collection occurred from December 1, 2024, to February 10, 2025. Maternal blood samples were analyzed using atomic absorption spectrophotometry to determine serum concentrations of copper, zinc, selenium, and chromium. Neonatal outcomes were assessed via standard clinical evaluations: heart rate and respiratory rate were measured immediately postpartum, and Apgar scores were recorded at five minutes. Statistical analyses included Pearson correlation and multiple linear regression to assess associations between maternal factors and neonatal outcomes. Bivariate and multivariate analyses indicated limited but noteworthy associations. Maternal serum chromium levels were significantly associated with increased neonatal respiratory rate (p = 0.026), suggesting a possible stimulatory or stress-related effect.